Age transition of tuberculosis incidence and mortality in Brazil - Flávio Chaimowicz
OBJECTIVE: Before the Aids pandemic, demographic transition and control programs prompted a shift in the age of incidence of tuberculosis from adults to older people in many countries. The objective of the study is to evaluate this transition in Brazil. METHODS: Tuberculosis incidence and mortality data from the Ministry of Health and population data from the Brazilian Bureau of Statistics were used to calculate age-specific incidence and mortality rates and medians. RESULTS: Among reported cases, the proportion of older people increased from 10.5% to 12% and the median age from 38 to 41 years between the period of 1986 and 1996. The smallest decrease in the incidence rate occurred in the 30--49 and 60+ age groups. The median age of death increased from 53 to 55 years between 1980 and 1996. The general decline in mortality rates from 1986 to 1991 became less evident in the 30+ age group during the period of 1991 to 1996. A direct correlation between age and mortality rates was observed. The largest proportion of bacteriologically unconfirmed cases occurred in older individuals. CONCLUSIONS: The incidence of tuberculosis has begun to shift to the older population. This shift results from the decline in the annual risk of infection as well as the demographic transition. An increase in reactivation tuberculosis in older people is expected, since this population will grow from 5% to 14% of the Brazilian population over the next 50 years. A progressive reduction in HIV-related cases in adults will most likely occur. The difficulty in diagnosing tuberculosis in old age leads to increased mortality.